Future directions in biodiversity and zoological research (Zoological Records and Reviews, 2025)
Biodiversity and zoological research stand at a pivotal juncture: the convergence of unprecedented technologicalcapabilities -- whole-genome sequencing, artificial intelligence, Earth observation, autonomous sensor networks, andglobal open data infrastructure -- with the most severe biodiversity crisis in human history and the most ambitiousinternational conservation commitments ever adopted (Kunming-Montreal Global Biodiversity Framework; EUBiodiversity Strategy 2030; Nature Restoration Law) creates both a mandate and an opportunity to transform the scopeand impact of zoological science. This review synthesises insights from 158 forward-looking analyses and expertelicitation studies (2015-2025) to identify ten priority research directions for European biodiversity and zoologicalresearch in the 2025-2040 decade. Priority directions are evaluated across four dimensions -- scientifictransformativeness, conservation management impact, technological readiness, and current European research capacity-- and ranked by composite priority score. The highest-priority directions identified are: (1) AI-enabled real-timebiodiversity monitoring using integrated sensor networks; (2) functional genomics of climate adaptation for proactiveconservation management; (3) mechanistic multi-stressor prediction frameworks transferable across species andsystems; (4) rewilding ecology and trophic cascade quantification; and (5) One Health surveillance integrating wildlife,domestic animal, and human disease monitoring. Structural barriers -- taxonomic expertise erosion, funding cyclemismatches, open data gaps, and the research-policy translation deficit -- are analysed alongside institutional solutions.A proposed European Zoological Research Agenda 2025-2040 aligns the ten priority directions with EU Horizon Europeprogramming, national research council priorities, and EU biodiversity policy implementation requirements.
Keywords: EU Biodiversity Strategy; Kunming-Montreal GBF; research agenda; rewilding; One Health; functional genomics; AI monitoring; zoological science; biodiversity research; future directions